'You betrayed us': Ethnic celebrity gossip in diasporic women's online communities. (June 2022) - Lee, Jin; Lee, Claire Shinhea
This article examines a relationship between ethnic celebrities and diasporic communities by focusing on one case of Korean diasporic women gossiping about Korean actress Seo Min-jung. After a 10-year hiatus following her sudden migration to the United States and marriage to a Korean American dentist in 2007, Seo made a successful comeback to show business by starring in Korean reality shows and opening her Instagram account. Seo's struggles as a Korean immigrant woman/housewife/mother, portrayed in TV shows and on Instagram, positively resonated with diasporic Korean women's online communities (DKWOC). This positive discourse around Seo, however, transformed into celebrity bashing when her Instagram scandal happened in 2019. We trace the change of gossip around Seo in DKWOC concerning Korean diasporic women's identity and status. We argue that DKWOC members' gossiping of Seo functions as a way of coping with their situation, as they come to recognise the class difference between themselves and Seo and feel disempowered by their dissatisfying circumstances as immigrants.